2016
DOI: 10.4238/gmr.15027590
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the LPL gene and their association with growth traits in Jiaxian cattle

Abstract: ABSTRACT. Previous studies showed that the lipoprotein lipase (LPL) gene was involved in metabolism and transport of lipids, suggesting that the LPL is a potential candidate gene affecting growth traits in animals. The aim of this study was to identify polymorphism in the bovine LPL gene and analyze its possible association with growth traits in 218 randomly selected Jiaxian cattle. We used DNA sequencing to identify single nucleotide polymorphisms (SNPs) in the LPL gene. A sequence analysis revealed three SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Milk performance is considered to be primary economic trait in dairy cattle, which is regulated by a series of factors, such as inheritance, age, diet, location and other random environment factors. Accumulating genome‐wide association studies (GWAS) indicated that a numbers of candidate genes (i.e., Toll‐like receptor 4, UDP‐glucose dehydrogenase, complement component 4) are involved in complex mechanisms, thereby altering milk performance traits (Gui et al., 2016; Li et al., 2015; Palombo et al., 2018), Here, we detected significant SNPs within the SAA2 gene that potentially influence milk composition and yield in Chinese dairy cattle, which could be used as a genetic marker aiming towards long‐term improvement in production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk performance is considered to be primary economic trait in dairy cattle, which is regulated by a series of factors, such as inheritance, age, diet, location and other random environment factors. Accumulating genome‐wide association studies (GWAS) indicated that a numbers of candidate genes (i.e., Toll‐like receptor 4, UDP‐glucose dehydrogenase, complement component 4) are involved in complex mechanisms, thereby altering milk performance traits (Gui et al., 2016; Li et al., 2015; Palombo et al., 2018), Here, we detected significant SNPs within the SAA2 gene that potentially influence milk composition and yield in Chinese dairy cattle, which could be used as a genetic marker aiming towards long‐term improvement in production.…”
Section: Resultsmentioning
confidence: 99%
“…The intronic g.18341 C>T of the lipoprotein lipase ( LPL ) gene was significantly correlated with withers height and chest depth in Nanyang cattle (Gui et al., 2016). Currently, it was speculated that 14061A>G and g.3208C>T may impact the biological function, resulting in an alteration in phenotype of mammal.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the g.2694 C > T and g.3801 T > C mapping on intronic SNPs of max dimerization protein 3 (MXD3) influenced on several growth traits in two Chinese indigenous beef cattle [23]. The intronic g.18341 C > T of the lipoprotein lipase (LPL) was significantly correlated with withers height and chest depth in Nanyang cattle [24].…”
Section: Discussionmentioning
confidence: 99%